Mutation in phcA Enhanced the Adaptation of Ralstonia solanacearum to Long-Term Acid Stress - Liu, Ying; Tan, Xi; Pan, Yanxin; Yu, Jiamin; Du, Yiran; Liu, Xiaojiao; Ding, Wei (Frontiers in Microbiology, 2022)
Bacterial wilt, caused by the plant pathogen Ralstonia solanacearum, occurs more severely in acidified soil according to previous reports. However, R. solanacearum cannot grow well in acidic environments under barren nutrient culture conditions, especially when the pH is lower than 5. With the worsening acidification of farmland, further determination of how R. solanacearum adapts to the long-term acidic environment is worthwhile. In this study, experimental evolution was applied to evaluate the adaptability and mechanism of the R. solanacearum experimental population responding to long-term acid stress. We chose the CQPS-1 strain as the ancestor, and minimal medium (MM medium) with different pH values as the culture environment to simulate poor soil. After 1500 generations of serial passage experiments in pH 4.9 MM, acid-adapted experimental strains (denoted as C49 strains) were obtained, showing significantly higher growth rates than the growth rates of control experimental strains (serial passage experiment in pH 6.5 MM, denoted as C65 strains). Competition experiments showed that the competitive indices (CIs) of all selected clones from C49 strains were superior to the ancestor in acid environment competitiveness. Based on the genome variation analysis and functional verification, we confirmed that loss of function in the phcA gene was associated with the acid fitness gain of R. solanacearum, which meant that the inactivation of the PhcA regulator caused by gene mutation mediated the population expansion of R. solanacearum when growing in an acidic stress environment. Moreover, the swimming motility of acid evolution strains and the phcA deletion mutant was significantly enhanced compared to CQPS-1. This work provided evidence for understanding the adaptive strategy of R. solanacearum to the long-term acidic environment.